Preference Analysis and Nutritional Profile of Yellowfin Tuna (Thunnus albacares) Fish Cake with the Addition of Corn Flour - Fitriany Abdulsalam; Sitkun Deni; Azis Husen (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2026)
Yellowfin tuna (Thunnus albacares) is a highly nutritious fish, rich in protein and low in fat. However, its quality degrades quickly, prompting the need for processing diversification. One such process is making otak-otak, a traditional fish cake typically made with tapioca flour. This study introduced an innovation by adding cornstarch as a binding agent to evaluate its effects on the organoleptic properties and chemical composition (proximates) of the fish otak-otak. The aims were to assess panelists’ preferences based on taste, texture, aroma, and appearance, and to analyze the proximate composition water, protein, fat, ash, and carbohydrates. The research was carried out at the Fish Product Technology Laboratory, Muhammadiyah University of North Maluku, using fresh bigeye tuna meat. The products were prepared by mixing 150 g tapioca flour with varying amounts of cornstarch (0%, 25%, 50%, 75%), then steamed, partially fried, and tested by 25 untrained panelists using a hedonic scale. Data analysis involved ANOVA, DMRT, Kruskal-Wallis, and Mann-Whitney tests. Results showed that adding cornstarch significantly impacted both sensory qualities and chemical composition. The treatment without cornstarch (A0) received the highest scores on taste, aroma, texture, and appearance, indicating higher preference. Proximate analysis revealed that the highest protein content was in A0 (20.37%), while A2 had the lowest water content (57.98%) and the highest carbohydrate level (23.22%). Overall, products without cornstarch were more favored, although higher cornstarch levels increased carbohydrate content and decreased sensory appeal.